Factors associated with concurrent wasting and stunting among children 6–59 months in Karamoja, Uganda - Adobea Odei Obeng-Amoako, Gloria; Karamagi, Charles Amnon Sunday; Nangendo, Joanita; Okiring, Jaffer; Kiirya, Yerusa; Aryeetey, Richmond; Mupere, Ezekial; Myatt, Mark; Briend, André; Nakayaga Kalyango, Joan; Wamani, Henry (Maternal and Child Nutrition, 2021)
Children with concurrent wasting and stunting (WaSt) and children with severe wasting have a similar risk of death. Existing evidence shows that wasting and stunting share similar causal pathways, but evidence on correlates of WaSt remains limited. Research on correlates of WaSt is needed to inform prevention strategies. We investigated the factors associated with WaSt in children 6–59 months in Karamoja Region, Uganda. We examined data for 33,054 children aged 6–59 months using June 2015 to July 2018 Food Security and Nutrition Assessment in Karamoja. We defined WaSt as being concurrently wasted (weight-for-height z-scores <−2.0) and stunted (heightfor- age z-score <−2.0). We conducted multivariate mixed-effect logistic regression to assess factors associated with WaSt. Statistical significance was set at p < 0.05. In multivariate analysis, being male (adjusted odds ratio [aOR] = 1.79; 95% confidence interval [CI] [1.60–2.00]), aged 12–23 months (aOR = 2.25; 95% CI [1.85–2.74]), 36–47 months (aOR = 0.65; 95% CI [0.50–0.84]) and 48–59 months (aOR = 0.71; 95% CI [0.54–0.93]) were associated with WaSt. In addition, acute respiratory infection (aOR = 1.30; 95% CI [1.15–1.48]), diarrhoea (aOR = 1.25; 95% CI [1.06–1.48]) and malaria/fever (aOR = 0.83; 95% CI [0.73–0.96]) episodes were associated with WaSt. WaSt was significantly associated with maternal underweight (body mass index <18.5 kg/m2), short stature (height <160 cm), low mid-upper arm circumference (MUAC <23 cm) and having ≥4 live-births. WaSt was prevalent in households without livestock (aOR = 1.30; 95% CI [1.13–1.59]). Preventing the occurrence of WaSt through pragmatic and joint approaches are recommended. Future prospective studies on risk factors of WaSt to inform effective prevention strategies are recommended.
Keywords: Concurrent wasting and stunting; Factors associated with WaSt; Stunting; Uganda; Wasting